(untitled) - World Health Organization (Geneva, 1996)
The book has two parts. Part one provides a practical guide to the relief of cancer pain, concentrating on drug treatment as the mainstay of pain management. The most extensive section sets out detailed guidelines for the selection and prescribing of non-opioid analgesics, opioid analgesics, drugs for neuropathic pain, and adjuvant drugs for the treatment of adverse effects, the enhancement of pain relief and the management of concomitant psychological disturbances. Information ranges from explanations of how specific drugs work, through the precautions to take in the presence of certain disorders, to a list of factors that influence the effectiveness of opioids. Concerning the use of opioids, readers are reminded that psychological dependence does not occur in cancer patients and that the only correct dose of morphine is the one that relieves the pain.
Keywords: Narcotherapy,Neoplams,Pain,Palliative treatment; Drug therapy,Drug therapy